Ownership structures and firm performance: Does East Asian corporate governance recovery work? - Warokka, Ari; Abdullah, Haim Hilman; Duran, Juan Jose (World Business Institute (WBI), 2012)
Few prior studies investigated a further link between ownership structure and firm performance in terms of post Asian Financial Crisis in 1997-1998 and explored the impact of the corporate governance recovery program. Using an agency framework, this research argued that the distribution of equity ownership among top managers and external block holders had a significant relationship with leverage and firm performance, and there was reverse causality effect between ownership structure, capital structure, and firm performance.The paper tested five hypotheses and used 532 East Asian companies’ financial data in 2000-2001 (a starting period of the recovery program) of seven most affected countries. Based on statistical analysis, the study revealed the positive impacts of corporate governance recovery indicated by an increasing of cost efficiency in monitoring and controlling the management. It also supported the managerial ownership as one way to reduce conflict of interest between shareholder and manager and increase firm value.